TIPE POLA ASUH ORANG TUA YANG BERHUBUNGAN DENGAN PERILAKU BULLYING DI SMA KABUPATEN SEMARANG - Rida Nurhayanti; Dwi Novotasari; - Natalia (Universitas Muhammadiyah Semarang, 2013)
Bullying children tend to do juvenile delinquency, and other criminal behavior. Parenting style also plays a role in the process of socialization on children to show bullying behavior. The objective of this research is to determine the type of parenting pattern concerning bullying behavior at Sudirman Islamic Senior High School at Ambarawa, Semarang Regency. The method of this research was descriptive correlation using cross sectional approach to 766 students as the population, and 88 respondents as the samples. The data collecting technique used questionnaires about the type of parenting pattern and bullying behavior. Data analysis used chi square analysis. The findings of this research reveal that the type of parenting pattern felt by students is mostly democratic than authoritarian and permissive parenting pattern as many as 40 students (45.5%). Bullying behavior done by students is mostly mild as many as 51 students (58.0%). There is a relation between tehe type of parenting pattern with bullying behavior in Sudirman Islamic Senior High School at Ambarawa, Semarang Regency (p value 0.027). An advice for parents should exemplify a positive attitude, be flexible according to the situation and ongoing conditions, understand children as young teenagers who areexperiencing a period of transition and change and experiencing rapid growth in many ways, both physically and mentally, respecting and giving support to childrent.Keywords: type of parenting pattern, bullying behavior